Endoscopic characteristics in predicting prognosis of biopsy-diagnosed gastric low-grade intraepithelial neoplasia. Issue 1 (5th January 2022) - Zou, Long; Jiang, Qingwei; Guo, Tao; Wu, Xi; Wang, Qiang; Feng, Yunlu; Zhang, Shengyu; Fang, Weigang; Zhou, Weixun; Yang, Aiming
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Endoscopic biopsy can underestimate gastric malignancies as low-grade intraepithelial neoplasia (LGIN). Definitively diagnosed LGIN would progress. This study aimed to evaluate predictive factors to identify malignancies misdiagnosed as LGIN by biopsy and LGIN at high risk of progression. Methods: The clinical records of patients diagnosed with gastric LGIN by endoscopic biopsy who underwent at least two endoscopies during the first year of follow-up between 2007 and 2017 were retrospectively collected. Three endoscopists reviewed photographs of the initial endoscopy, described lesion characteristics, and made endoscopic diagnoses. Logistic regression was used to analyze predictors to identify malignancies underestimated as LGIN. A receiver operating characteristic curve was used to evaluate the diagnostic accuracy of these predictors. Patient clinical outcomes of follow-up >1 year were collected. Kaplan–Meier estimates with log-rank tests and Cox proportional hazards regression were used to analyze predictors of progression. Results: Overall, 48 of 182 (26.4%) patients were proven to have malignancies. A single lesion, a large lesion size, and marked intestinal metaplasia (IM) were independent predictors of initially misdiagnosed malignancies. The area under the curve of these predictors was 0.871, with a sensitivity of 68.7% and specificity of 92.5%. Twelve of 98 patients (12.2%) progressed during the 33-month median follow-up period. A whitish appearance, irregular margins, marked IM, and histological diagnosis of LGIN more than twice within the first year were predictors for progression. Conclusions: Lesions diagnosed as LGIN by biopsy with marked IM and other predictors above should be prudently treated for high potential to be malignancies or progress. Endoscopic follow-up with repeated biopsies within the first year is recommended.